Dos amigos y un destino trágico. Recursos literarios de Plutarco en la escena de Alejandro y Clito - Pérez-Jiménez, Aurelio (My University, 2019)
As a convinced Platonist, Plutarch mistrusts the didactic value of poetry, including theater; but, nevertheless, as an accomplished narrator of the stories of so many characters of Greek and Roman Antiquity whose life was full of dramatic moments, we are accustomed to see him projecting on biography his profound knowledge of the strategies of Greek drama. The anecdote of Clitus’death by Alexander whose development begins with the friendly attitude of the king towards his general is not an exception. Certainly, in the presentation of this anecdote, we recognize the ingredients with which the Greek tragedy enriches the action of its heroes: the fortune; the fulfillment of destiny; the imposibility to avoid a tragic end by the individuals despite their knowledge of the future and their recourse to religious instruments to change it; the proud attitude of the hero confident in the strength of his ideals; and, at the end, the tragic irony and the fatal outcome. Plutarch, intervening with his literary creativity in the story, which we know by other sources, also puts at stake here all the resources of his style at the service of this scene that reveals the rigors of human life and the difficult links between the characters involved in the anecdote.
Keywords: Plutarco; Anécdotas de Plutarco; Análisis literario; Vida de Alejandro; Clito